Pengaruh Pola Asuh Orang Tua Terhadap Agresivitas pada Persepsi Siswa Kelas IX - utami, wening suko (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The purpose of this study was to determine how much the influence of the authoritarian, democratic, and permissive parenting to the aggressiveness of the students.In this study used a sample of students class IX in Kesatrian 2 Junior High School Semarang as many as 66 students of 228 students. The variables studied in this research were variable of parenting and aggressiveness. The data collection is done by using a questionnaire. Data were analyzed using descriptive analysis and multiple regression technique. The results of this multiple regression analysis is Y = 21.836 + 1.073 X1 + 0.393 X2 + 0.963 X3. There is a simultaneous contribution of 62.7%. There was effect of positive correlation parenting authoritarian, democratic and permissive to partially aggressiveness. The conclusion of this study, there was positive corelation foster parents towards aggressiveness simultaneously or partially.